The Dilemma of Natural Resources: Economic Opportunities and Challenges Post-Conflict - Hajad, Vellayati (International Journal of Energy Economics and Policy, 2020)
The aim of this paper is to find out how natural resources are able to strengthen economic recovery after the conflict while at the same time maintaining peace. Natural resources in the form of coal mining are a new arena for former rebels to create greater economic opportunities after the conflict. The objective of the economic sovereignty of the rebels is to preserve the social and political existence of the community that had faded as a result of the peace agreement signed in 2005, which caused the rebels to lose many of the previously owned effects created by the possession of weapons, troops and loyalist support. This study uses a qualitative method with a case study approach in West Aceh, Indonesia, by interviewing former rebels on economic activities before and after the conflict. The conclusion of this study shows that former rebels use limited access to natural resources as an opportunity for economic recovery and making coal mining one of the arenas of a new economic struggle to replace armed struggle. Keywords: natural resources, coal mining, economic opportunity, rebels, post-conflict JEL Classifications: O13, P28, Q34 DOI: https://doi.org/10.32479/ijeep.10326